Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4279156 10.5281/zenodo.4279156 2129771:XYEJSVYW 2339240:59XYS4NB 2339240:EETQSD8S 2339240:HZTGKNN9 2405685:2W6A2G3H 2405685:6KDDB8UA 2405685:MS5GH9KJ 2405685:S9MFQ8KB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
previousshortDOI: 10/ghgngk previousshortDOI: 10/ghgngk previousDOI: 10.5281/zenodo.3631750 previousshortDOI: 10/ghgngk EdTechHub.Copy: 2129771:5EWDQDIA EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngk KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631750 10.53832/edtechhub.0013 10/ghgngk 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:978RP7D4 2405685:VM6NXYF3
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
ZenodoArchiveID: 3966976 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3966976 2129771:XMGQ4JQJ 2339240:L5RLM582 2339240:R72E853W 2405685:T2W7MU3K 2405685:U49W6LTF 2405685:ZI8PHKCC
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
previousshortDOI: 10/ghgngg previousshortDOI: 10/ghgngg previousDOI: 10.5281/zenodo.3631746 previousshortDOI: 10/ghgngg EdTechHub.Copy: 2129771:EHFUXJQC EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngg KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631746 10.53832/edtechhub.0011 10/ghgngg 2129771:EHFUXJQC 2129771:YHNWVMB3 2339240:94ZP3EK4 2339240:FIDI5TC2 2405685:39DIRNE9 2405685:HH3QKBIF 2405685:I3BV48CX 2405685:ITL9PIC3 2405685:K8BSWYFM 2405685:KF9F48ID 2405685:N68MMAPR 2405685:P5Y5GMFN 2405685:SC5NHA65 2486141:TAY7LNB6
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
ZenodoArchiveID: 3631748 previousshortDOI: 10/ghgngh previousshortDOI: 10/ghgngh previousDOI: 10.5281/zenodo.3631748 previousshortDOI: 10/ghgngh EdTechHub.Copy: 2129771:UEUAKMXJ EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngh KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631748 10.53832/edtechhub.0012 10/ghgngh 2129771:UEUAKMXJ 2339240:94ZP3EK4 2339240:E62J77SP 2339240:MM2SDXUM 2339240:S4UAH7Q3 2405685:3AV6MSKJ 2405685:DQWJLRN5 2405685:H9W2X3KM
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (2020)
Presentation given at BE2, 2020-10-06.
shortDOI: 10/ghgnf4 KerkoCite.ItemAlsoKnownAs: 10/ghgnf4 2129771:WPJL8SN3 2339240:7TXCEBE6 2405685:5VQMVDB9
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
ZenodoArchiveID: 4706074 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706074 2339240:8TCJQBLC 2405685:5DWI862Y 2405685:ZWLE9BLR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
previousshortDOI: 10/ghgk69 previousDOI: 10.5281/zenodo.3911651 shortDOI: 10/ghgk69 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911651 10.53832/edtechhub.0034 10/ghgk69 2339240:4SKXJ887 2405685:ED7RBJHG 2405685:VSMMBMQE
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

E-Learning in Bangladesh: A Study of Teachers’ Behavioral Orientation and Affective Alignment in the Post-New Normal - Shamim Miah, A.S.M; Rasel Kabir, Md; Sultana, Sarmin (Contemporary Research in Education and English Language Teaching, 2020)
This study explores the teachers’ behavioral and affective orientation to e-learning that is in practice at all the levels of education in Bangladesh i.e. primary school, secondary school, higher secondary school, college, and university. By investigating the reasons for such disarray, it proposes solutions to overcome them. It acquired its data through online surveys followed by quantitative analysis through descriptive inferential analogies of the logarithmically represented findings. The result of the study documents that teachers’ preparation, technological know-how and adaptation to the e-learning platforms, their methods of teaching, measurement of outcomes, and mapping of curricula suggest that e-learning in Bangladesh is vitiated due to the diffusion in the teaching staff demographics and diluted apprehension of the e-learning. The paper’s primary findings show that Bangladesh’s progress from Education 1.0 to Education 3.0 is more affective and behavioral than cognitive in the implementation; wherein, the very concept of e-learning is diluted or spun around the idea of education via some usage of technology only, more specifically web conference applications which is indicative of Education 2.0 practices. There is no distinction made that separates online learning from e-learning, e-learning from distance and distance from blended learning, etc. in the current environment.
KerkoCite.ItemAlsoKnownAs: 10.33094/26410230.2020.21.16.35 10/gj37h5 2339240:A7RYDPHH 2405685:KVRAQU2P

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Sandboxes: My experience participating in the sandbox alpha - Kumasewera, Pilirani (EdTech Hub, 2020)
This is the third in this series about our sandboxes. If you haven’t already, read about our approach to experimentation and how we tested our sandbox strategy out in Malawi.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2405685:CE3XH7JY
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Identifying Effective Teachers: Lessons from Four Classroom Observation Tools - Filmer, Deon; Molina, Ezequiel; Wane, Waly (Research on Improving Systems of Education (RISE), 2020)
Four different classroom observation instruments—from the Service Delivery Indicators, the Stallings Observation System, the Classroom Assessment Scoring System, and the Teach classroom observation instrument—were implemented in about 100 schools across four regions of Tanzania. The research design is such that various combinations of tools were administered to various combinations of teachers, so these data can be used to explore the commonalities and differences in the behaviors and practices captured by each tool, the internal properties of the tools (for example, how stable they are across enumerators, or how various indicators relate to one another), and how variables collected by the various tools compare to each other. Analysis shows that inter-rater reliability can be low, especially for some of the subjective ratings; principal components analysis suggests that lower-level constructs do not map neatly to predetermined higher-level ones and suggest that the data have only a few dimensions. Measures collected during teacher observations are associated with student test scores, but patterns differ for teachers with lower versus higher subject content knowledge.
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISEWP_2020/045 2405685:DSRXVH6M 2561267:ZFIFPNTP
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4